The Role of Servant Leadership in Enhancing Teacher Job Satisfaction: A Study of School Organizational Behavior Mediated by Workload and Work Discipline - Ika Juliana Panjaitan; Agus Salim Salabi (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study aims to evaluate and analyze the strategic role of servant leadership by school principals in directly influencing teachers’ job satisfaction, as well as to examine the mediating role of workload and work discipline in bridging this relationship among teachers at Sukma Bangsa Private Junior High School. Methodology: This study employed a quantitative method with a descriptive survey design. The research subjects consisted of a total sample of 50 teachers at Sukma Bangsa Private Junior High School in Lhokseumawe, selected through a saturation sampling technique. Data were collected primary through a structured questionnaire survey using a 5-point Likert scale and secondary through documentation. Data analysis was performed using Structural Equation Modeling based on Partial Least Squares operated via SmartPLS software to test the measurement model and structural model. Main Findings: The analysis demonstrates that servant leadership exerts a direct, positive, and significant influence on teachers' job satisfaction, workload, and work discipline. Concurrently, teacher job satisfaction is empirically unaffected by either work discipline or workload. Furthermore, the mediation analysis confirms that workload and work discipline fail to mediate the relationship between servant leadership and job satisfaction, whether partially or simultaneously. Novelty/Originality of this study: Contrasting conventional organizational behavior theories that treat workload strictly as a negative stressor, this study offers a conceptual novelty under a servant leadership framework, increased task involvement is perceived positively by teachers as a form of professional trust and empowerment. Socially and educationally, this study contributes by affirming that teachers' emotional well-being within schools is not dictated by formal structural controls disciplinary rules or work volume, but rather by the fulfillment of psychological needs fostered through supportive, humanistic, and empathetic interpersonal relationships from school leadership.